OPTIMIZATION OF CHECKSUM ENCODING FOR TRANSMISSION AND STORAGE OF DIGITAL INFORMATION - Samofalov , K. G.; Al-Hawaldi, Ali Tawfiq Okla; Lazuchenkov, D. V. (Problems of Informatization and Control, 2021)
The article proposes a new approach to improving the efficiency of detecting data transmission errors using a checksum by optimizing its coding based on special differential Boolean transformations. Two methods of obtaining such conversions have been developed, examples of functions for encoding the checksum are given.